Assessing medical mistrust in organ donation across countries using item response theory. (October 2022) - Ghoshal, Arunangshu; O'Carroll, Ronan E; Ferguson, Eamonn; Shepherd, Lee; Doherty, Sally; Mathew, Mary; Morgan, Karen; Doyle, Frank
Although medical mistrust (MM) may be an impediment to public health interventions, no MM scale has been validated across countries and the assessment of MM has not been explored using item response theory, which allows generalisation beyond the sampled data. We aimed to determine the dimensionality of a brief MM measure across four countries through Mokken analysis and Graded Response Modelling. Analysis of 1468 participants from UK ( n = 1179), Ireland ( n = 191), India ( n = 49) and Malaysia (n = 49) demonstrated that MM items formed a hierarchical, unidimensional measure, which is very informative about high levels of MM. Possible item reduction and scoring changes were also demonstrated. This study demonstrates that this brief MM measure is suitable for international studies as it is unidimensional across countries, cross cultural, and shows that minor adjustments will not impact on the assessment of MM when using these items.